The Effectiveness of Take and Give Learning Model in Improving Reading Comprehension Learning Outcomes of Descriptive Text Materials in Grade IV Students - Mey Kartika; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
This study aims to determine the effectiveness of the Take and Give learning model in improving reading learning outcomes in understanding descriptive text materials in grade IV students of State Elementary School 078 Panyabungan, Mandailing Natal Regency. The background of this study departs from the problem of low student learning outcomes in understanding descriptive texts, which is caused by the lack of active interaction in learning and the dominance of lecture methods that are still teacher-centered. For this reason, it is necessary to apply a learning model that is able to activate students in a participatory manner. The Take and Give model is a cooperative learning strategy that emphasizes the exchange of information between students. Each student is given a card containing learning materials, then shares information with fellow students in turns. This model is believed to train communication skills, foster self-confidence, and improve understanding of reading content through the process of repetition and re-explanation. This type of research is experimental research with a One Group Pretest-Posttest design. The research sample was all 28 fourth-grade students of SD Negeri 078 Panyabungan. The instruments used included multiple-choice learning outcome tests and student activity observation sheets. The data were analyzed using descriptive and inferential statistics. The results showed that there was a significant increase in student learning outcomes after the Take and Give learning model was implemented. The average posttest score for students was higher than the pretest score. In addition, student learning activities also increased, as seen from their active involvement in discussions and exchange of information during the learning process. The evaluation also showed that most students achieved scores above the Minimum Completion Criteria (KKM), and the classical learning completion rate reached more than 85%